Human Protoparvovirus DNA and IgG in Children and Adults with and without Respiratory or Gastrointestinal Infections - Mohanraj Ushanandini; Jokinen Maija; Thapa Rajita Rayamajhi; Paloniemi Minna; Vesikari Timo; Lappalainen Maija; Tarkka Eveliina; Nora-Krukle Zaiga; Vilmane Anda; Vettenranta Kim; Mangani Charles; Oikarinen Sami; et al. (MDPI, 2022)
Three human protoparvoviruses, bufavirus (BuV), tusavirus (TuV) and cutavirus (CuV), have recently been discovered in diarrheal stool. BuV has been associated with diarrhea and CuV with cutaneous T-cell lymphoma, but there are hardly any data for TuV or CuV in stool or respiratory samples. Hence, using qPCR and IgG enzyme immunoassays, we analyzed 1072 stool, 316 respiratory and 445 serum or plasma samples from 1098 patients with and without gastroenteritis (GE) or respiratory-tract infections (RTI) from Finland, Latvia and Malawi. The overall CuV-DNA prevalences in stool samples ranged between 0-6.1% among our six patient cohorts. In Finland, CuV DNA was significantly more prevalent in GE patients above rather than below 60 years of age (5.1% vs 0.2%). CuV DNA was more prevalent in stools among Latvian and Malawian children compared with Finnish children. In 10/11 CuV DNA-positive adults and 4/6 CuV DNA-positive children with GE, no known causal pathogens were detected. Interestingly, for the first time, CuV DNA was observed in two nasopharyngeal aspirates from children with RTI and the rare TuV in diarrheal stools of two adults. Our results provide new insights on the occurrence of human protoparvoviruses in GE and RTI in different countries.